PERANAN STRATEGI PEMASARAN DALAM MENINGKATKAN PENJUALAN PRODUK PERUSAHAAN - Ghazendra Sadika Putra Pratama; Eloh Bahiroh (Bajang Institute, 2023)
This thesis is motivated by the number of competition among entrepreneurs, especially traders to attract consumers so that it can increase sales. And one way is to implement a marketing strategy. Marketing strategy must be done effectively so that sales can increase. Marketing activities geneally focus on products ,pricing ,distributed policies, and promotional ways in which this is known as the marketing mix . Marketing mix activity plays an important role for the survival of a company. Marketing strategy is choosing market, product, distribution and promotion; the most effective marketingstrategy is promotion, promotion through social media and radio; Vanhelenshop marketing strategy is seen from the perspective of Islamic already according to this matter seen from the products sold already halal, buyers can choose the product according to taste and in promotion is not exaggerate and does not cover product defect.